Remainder - McCarthy,Tom (Alma Books, 2016)
Film Tie-in edition to be published to coincide with the release of the film Remainder. Praised by Zadie Smith as "one of the great English novels of the past ten year", this edition contains a foreword by American scholar McKenzie Wark.